The Role of Social Studies Teacher to Improve Student Question Skills - Nurhasanah, Almah; Widyanti, Triani; Mulyana, Eldi (Institut Pendidikan Indonesia, 2022)
The role of the teacher in applying the skill of asking questions during learning. The teacher is an important component in the teaching and learning process. Teachers have a role to form human resources who are professional and responsible for the education of their students, but many students are embarrassed to ask questions. Therefore, to overcome these problems, the Role of the Social Sciences Teacher is needed in Growing Questioning Skills. The goal to be achieved from this research is to find out the role of the social studies teacher in cultivating questioning skills, student responses to the social studies teacher's role in cultivating questioning skills and the constraints experienced. The method used in this research is a qualitative method using a descriptive study approach. Data collection techniques in this study used observation, interviews and documentation. The data analysis technique consists of three stages, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions. The results of the study showed that the teacher's role in cultivating questioning skills in Class VII social studies learning at SMPN 2 Tarogong Kidul Garut was quite good, students also performed well regarding the importance of the teacher's role. Students who ask questions will be given answers by the teacher and appreciation in the form of additional points that encourage other students to be active in class. The obstacle faced by the teacher is that there are still students who do not understand the material but are embarrassed to ask questions.